Ascorbic acid for reducing foliage discoloration in cut chrysanthemum - Hiremath, Varun M; Jain, Ritu (Indian Horticulture, 2021)
Owing to the steady increase in demand of flowers, floriculture has become one of the important commercial businesses in horticulture. Chrysanthemum is one of the topmost cut flowers earning high domestic as well as export value. Post-harvest management of cut flowers is very important to enhance their vase life and keep them attractive for a longer time after consumers purchase. Early wilting and yellowing of leaves are major problem resulting in loss of quality in chrysanthemum. Studies have proved the application of ascorbic acid as chemical preservative against foliage discoloration and petal wilting in lilium, red ginger, rose, carnation, etc. Yet, it is water soluble and cheaply available in market. In this regard, present study was carried out to study its influence on foliage discoloration and reported that the use of ascorbic acid as spray solution to reduce leaf yellowing and petal wilting in chrysanthemum. Ascorbic acid sprays will be helpful for consumers to keep the cut flowers fresh, turgid and attractive for longer time.